ANALISIS MODUL AJAR BAHASA INDONESIA KELAS VI SDN POLOKARTO 1 BERDASARKAN KARAKTERISTIK PESERTA DIDIK - Najaah, Lathifah Safiinatun; Muthmainnah, Annisa; Amelia, Febrisha Arya; Hardiana, Nina; Rahmani, Putri Miftakhul; Safitri (Jurnal Jaringan Penelitian Pengembangan Penerapan Inovasi Pendidikan (Jarlitbang), 2025)
This study aims to evaluate the Grade VI Bahasa Indonesia teaching module at SDN Polokarto 01 within the framework of the Merdeka Curriculum, focusing on its alignment with pedagogical principles such as differentiated learning, culturally responsive teaching (CRT), and Understanding by Design (UbD). A library research method was employed to analyze the module’s structure, content, and assessment instruments. The findings reveal that the module meets basic systematic requirements, including learning objectives, essential materials, and interactive activities aligned with students’ cognitive development. However, three critical weaknesses were identified: (1) the absence of diagnostic assessments to map individual student needs, contradicting the principles of differentiated learning; (2) questions and contextual materials lacking relevance to students’ local environment, neglecting CRT’s emphasis on cultural connections; and (3) misalignment of summative assessments with learning objectives, particularly in developing creative writing skills, which deviates from UbD’s backward design principles. The study recommends integrating diagnostic assessments, contextualizing materials using local examples (e.g., incorporating the case of Alas Karet Polokarto), and aligning assessments with learning objectives through holistic rubrics.